Realitas Media Sosial dalam Novel Egosentris Karya Syahid Muhammad sebagai Bahan Ajar Apresiasi Sastra di SMA - Noventi, Nindia Dwita; Cahyani, Dzikrina Dian; Hapsari, Theresia Pinaka Ratna Ning (Kajian Bahasa dan Sastra (KABASTRA), 2024)
This research is motivated by literary works which are a reflection of society that describes everyday reality. The Egocentric novel by Syahid Muhammad tells various realities, especially the reality of social media that occurs in society. This study aims: (1) to describe the reality of social media contained in the Egocentric novel by Syahid Muhammad, then correlated with the current reality, and (2) to produce teaching materials for learning literary appreciation in high school about the reality of social media in the Egocentric novel by Syahid Muhammad. This research is a qualitative research that is examined using the sociology of literature with a mimetic approach. The primary data source of this research is the novel Egocentric by Syahid Muhammad, while the secondary data source is obtained from news articles on the internet. The data of this research are sentences that contain the reality of social media in the novel Egocentric and their correlations in real life. Collecting data using literature study method with reading and note-taking techniques. The data analysis used the analytical description method. The results of the study found 20 social media reality data in the Egocentric novel by Syahid Muhamaad and their correlations in the real world, and produced teaching materials in the form of handouts for class XII SMA at KD 3.8 and 4.8.